2016
DOI: 10.1155/2016/3926941
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trabecular Bone on Peri-Implant Stress and Strain Based on Micro-CT Finite Element Modeling of Beagle Dog

Abstract: The objective of this investigation is to analyze the influence of trabecular microstructure modeling on the biomechanical distribution of the implant-bone interface. Two three-dimensional finite element mandible models, one with trabecular microstructure (a refined model) and one with macrostructure (a simplified model), were built. The values of equivalent stress at the implant-bone interface in the refined model increased compared with those of the simplified model and strain on the contrary. The distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…More thickness results in a decrease of the maximum stress values at the cortical bone . In addition, the trabecular bone microstructure can disperse the stress and strain and function as a load buffer through the trabecular network and the basal bone.…”
Section: Loading the Implant‐bone Interfacementioning
confidence: 99%
“…More thickness results in a decrease of the maximum stress values at the cortical bone . In addition, the trabecular bone microstructure can disperse the stress and strain and function as a load buffer through the trabecular network and the basal bone.…”
Section: Loading the Implant‐bone Interfacementioning
confidence: 99%
“…In one study analyzing the relationship between the quality of cortical bone and stress distribution, Kitagawa et al 37 found an inverse correlation between cortical bone thickness and the stress values encountered at the bone. In a FEA study, Liao and colleagues 38 concluded that trabecular bone can disperse the stress and strain generated by occlusal load to various degrees based on their coarseness and architecture, and serve as a buffer to loading. The macro and microgeometry of the implant fixture affects the nature and magnitude of load transferred to the bone‐implant interface.…”
Section: Occlusion As a Predisposing Factor For Peri‐implant Diseasementioning
confidence: 99%
“…Thus, mechanical loading can induce both a negative or positive effect for the net bone tissue. The exact mechanisms that determine either an anabolic or catabolic response to load are difficult to discern due to the multitude of factors involved, but may be related to the surrounding bone quality, 37,38 the magnitude and direction of forces, 39,40 as well as the macro and micro-geometry of the implant fixture. 41…”
Section: Bone Remodeling and Occlusal Loadmentioning
confidence: 99%
“…The total contact area between the implant and bones of implant I is 214.5 mm 2 , which exceeds type (2) ITI commercial implant by about 42%. The improvements for both types (1) and (2) implants would undoubtedly enhance the osseointegration [ 41 , 42 ], which would help to prevent damage to the bone [ 43 ]. Thus, implant IV in case (1) and implant I in case (2) are regarded as the implants with the best healing chamber under the given loads.…”
Section: Application To Dental Implants In Posterior Maxillary Bonmentioning
confidence: 99%